Socialization of Zakat and The Calculation Model for KAPMI Students (Indramayu Students and Students Family) in Yogyakarta - Arum Puspitasari; Dian Melani; Febrian Rizky Hanafi; Liizza Diana Manzil; Millenia Ayu Nur Aini; Muhammad Romadon; Nafi’ah Firahmatillah; Pipit Nawasanga; Rahmadhany Putri Irwanda; Viliana Nanda Ilahi; Yeny Karina Khurniawanti (Journal of Islamic Economy and Community Engagement, 2021)
This study aims to assess the extent of adolescent knowledge about zakat and its calculations. Zakat itself is the third pillar of Islam, therefore we need to know in detail the types of zakat, its calculations, and to whom it is distributed. Zakat is a part of the property that must be issued by Muslims to be given to 8 asnaf as stated in the Qur'an and Sunnah. In Indonesia, there is the National Amil Zakat Agency (BAZNAS) whose task is to collect and distribute zakat, infaq and shodaqoh. BAZNAS has also arranged all zakat calculations from zakat fitrah, shares, agriculture, professions and many more.Keywords: Zakat, Zakat Calculation, BAZNAS.